Completing the state management of new rural construction in Cai Nuoc district, Ca Mau province - Truong , Minh Sang`; Phan , Thị Cúc (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
The article outlines the theoretical foundations of New Rural Development and evaluates the current state of public administration in this area, revealing several limitations: (i) Policy formulation; (ii) Planning and zoning; (iii) Implementation of legal documents; (iv) Inspection, examination, and supervision of local policy enforcement. The study conducted 50 surveys with local administrators to assess the effectiveness of state management in New Rural Development. From these findings, the article identifies existing issues and proposes solutions to improve public administration in this field at the local level.